Optimizing the Performance of Gakkum Satlantas Unit of Magelang Police in Implementing Tilang with the Sigap Mobile Application to Improve Public Services (Advances in Police Science Research Journal, 2024)
The Sigap Mobile application is a program based on the ETLE Handheld which was released by the Central Java Regional Police Traffic Directorate during the traffic anniversary which was inaugurated by the National Police Chief. The Sigap Mobile application is an application that can provide services to the public regarding legal certainty for traffic violators. In the implementation of fines with the Mobile Sigap application, not all violations have been confirmed by violators, this shows that the performance of the Magelang Police Satlantas Legal Action Unit in implementing fines with the Mobile Sigap application has not been optimal. The purpose of this study is to identify the implementation of fines with the Mobile Sigap application in order to improve public services by the Magelang Police Traffic Unit Unit and analyze the obstacles encountered in implementing fines with the Mobile Sigap application. The research location in this final project is the Magelang Police. The method used in this research is Field Research, which is a research method by looking directly at conditions in the field to understand the problem in depth and intact. Field Research combines observation techniques with open interviews, as well as examination and data collection if necessary. This research has a focus, namely how to optimize the Magelang Police Satlantas Unit in implementing fines with the Mobile Sigap application to improve public services. The data collection techniques used were interviews, observation and document studies. The results of this study indicate that the Magelang Police Satlantas Satlantas Unit in carrying out the ticketing process with the Mobile Sigap application is still not optimal because it can be seen from the existing data that of the violations caught by Mobile Sigap only 35% confirmed and completed the ticket. To achieve optimal results from the implementation of fines using the Mobile Sigap application, the participation of the community itself is also needed. In addition to imparting knowledge to the public regarding the Mobile Sigap mechanism, socialization is needed so that the public is aware of traffic rules, because in research many people try to trick the Gakkum Unit officers into carrying out fines with the Mobile Sigap application.
Keywords: Aplikasi Mobile Sigap; Tilang; Pelanggaran Lalu Lintas